DESTINATION MANAGEMENT AMUSEMENT IN RIAU PROVINCE - Rafif, Achmad Dzaky; Musthofa, Budiman Mahmud (UI Scholars Hub, 2019)
This Study discusses assignment management of natural tourism destination in riau province. At present the management of natural tourist destinations is very much needed in the tourism industry and in this Final Project Task Explains the author Also the management of natural tourist destinations the which intends to improve the quality of management of natural tourism destinations in Riau Province